PENGARUH BIAYA OPERASIONAL TERHADAP PROFITABILITAS PADA PERUSAHAAN UMUM DAERAH AIR MINUM KOTA MAKASSAR - Kosmas Mansur; Rahmawati; A Surmarlin K (Jurnal Humaniora & Sosial Sains, 2024)
This study aims to: Do ​​operating costs affect net profit margin (Y1), return on equity (Y2), return on assets (Y3) at the Makassar city drinking water company. This study uses a quantitative descriptive approach. The population in this study is 2019 - 2023, with the sampling technique used being saturated samples. The type of data is secondary data. The data collection techniques used are survey techniques, and documentation. The data were analyzed using normality tests, multicollinearity, heteroscedasticity, regression analysis, partial tests and coefficient of determination. Data analysis shows that the data is normally distributed, there is no multicollinearity, no heteroscedasticity. Regression analysis shows that: operating costs on net profit margin, return on equity, return on assets have a negative effect. Partial tests show that: operating costs on net profit margin, return on equity, return on assets have a significant effect. The determination coefficient test shows that: 1) operating costs have an effect of 60.6% on net profit margin; 2) operational costs have an influence of 88.2% on return on equity; 3) operational costs have an influence of 93.9% on return on assets.